Perbandingan waktu Pemulihan Blok Residual Pelumpuh Otot Rocuronium Dan Atracurium Pasca Anestesi Umum - , Desriyata Hia, dr.Muhdar Abubakar, SpAn.K ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: In Anesthesia, the effects of residual block often occur in the use of Neuormuscular block. The purpose of this study was to compare the recovery time block residual muscle paralyzing drug rocuronium with atracurium. The scope of the study were patients undergoing elective surgery with general anesthesia with techniq intubation endotracheal tube and control respirasi in GBST RSUP Dr. Sardjito Yogyakarta. Methods: The subjects consisted of 60 patients of male and female, age 18-65 years, ASA physical status I and II. Subjects were divided two groups, each group consisted of 30 patients. This research is done by an open randomized clinical trials (open randomized controlled trial). The study subjects were randomized into two groups. A group is a group that uses rocuronium group B using atracurium. Clinical criteria are achieved and TOF > 0,7 for extubation, in operating room, extubation was be done. Patients were monitoring in recovery room with a monitoring stimulator assement of TOF > 0,7 to 1. A group is a group that uses Rocuronium and group B is a group that uses Atracurium, with the main measurement is the time required for recovery of residual block. Results: The study found the recovery time on the residual block of rocuronium at 35.16 Â± 5.49 min and 34.83 Â± 5.79 for atracurium minutes. Statistically no significant difference in recovery time residuals in the second block of the research group. Conclusion: The recovery time both groups: Rocuronium and atracurium have the same recovery time.